Studies on Growth and Development of some Forest Tree Species in Red Mud Soil Balco Korba - Singh, Paramjeet, Jamaluddin; Purohit, Mamta (Indian Forester, 1988)
An attempt has been made to introduce suitable forestry species in red mud soils of Balco Korba to reclaim the waste soils which are depleted due to Industrial wastes. The results in detail have been discussed in this paper.